Respuesta :

Step-by-step explanation:

first you have to take all similar variable on the same side of the equation and the constants on the other side then solve the question .

example : -12x + 9 = -15x

-12x +15x = -9

3 x = -3

X = -3/3= -1

x = -1

like this you can solve all the other equation ..

Hope this will be helpful to you ..

plz mark my answer as brainlist if you find it useful..

Answer:

a)-3

b)2

c)27

you subtract 9 from both sides

-12x+9-9=-15-9

simplify=-12x=-15x-9

add 15x to both sides=-12x+15x=-15x-9+15x

Simplify=3x=-9

divide both sides by 3

3x/3=-9/3

x=-3

b)Step 1: Subtract 8.5x from both sides.

4.5x+11.5−8.5x=8.5x+3.5−8.5x

−4x+11.5=3.5

Step 2: Subtract 11.5 from both sides.

−4x+11.5−11.5=3.5−11.5

−4x=−8

Step 3: Divide both sides by -4.

−4x/−4=−8/−4

x=2

Answer: x=2

Step 1: Subtract 1/3x from both sides.

2/3x−9=1/3x

2/3x-9-1/3x=1/3x-1/3x

1/3-9=0

Step 2: Add 9 to both sides.

1/3x-9+9=0+9

1/3x=9

Step 3: Multiply both sides by 3.

3*(1/3x)=(3)*(9)

x=27

hope that was useful would appreciate a brainliest  if it helps you